Responding to patient deterioration: a medical records analysis - Mohamed Ludin, Salizar; Ruslan, Rusila (IIUM Press, 2018)
Objective: This paper reports the medical record analysis findings to identify nurses and junior doctors risk assessment and response to the incidence of deteriorating patient in general ward.